Cortical idiosyncrasies predict the perception of object size - Christina Moutsiana (Nature Communications, 2016)
Perceiving the size of objects is subjective. Here the authors show that these subjective differences in size perception can be explained by the individual variance in spatial tuning of neuronal populations in the primary visual cortex.